Insights into values and emotional wellbeing of medical students in the United Arab Emirates: a cross-sectional study - Alhashimi, Fatma Mustafa; Salim, Sara; Siddiqi, Warda; Jeyaseelan, Lakshmanan; Khan, Nusrat; Sultan, Meshal A. (Frontiers in Psychology, 2024)
Objective: To describe the difference in values among medical students from a first-year student' and final year student' perspective. In addition, it is designed to report associations and trends between personal values and overall emotional states.Methods: This is an analytical cross-sectional study that involved disseminating an online survey via email to first and final year students at the College of Medicine in Mohammed Bin Rashid University (MBRU) in Dubai, United Arab Emirates in December of 2023. The survey encompassed queries on demographics, the Life Values Inventory (LVI) and the Positive and Negative Affect Schedule (PANAS).The survey was completed by 84 students. About half of the participants were final year medical students (45/84; 53.6%) with the majority being females (70/84; 83.3%). Positive emotions were positively correlated to various life values, including belonging, scientific understanding, responsibility, and achievement (p<0.05). When comparing academic years, the scores of the life value of Achievement showed a significant correlation (p=0.04), with first-year students' mean (SD) of 12 (2) out of 15 compared to 11 (3) out of 15 for final-year students. Positive Emotions also exhibited a significant correlation (p=0.006), with first-year students' mean (SD) 40 ( 5) out of 50 compared to 36 (7) out of 50 for final-year students.This study adds to medical education research by exploring values and emotions, shedding light on factors shaping students' professional identities. Understanding these dynamics can aid in supporting future healthcare providers and by extension the patients for whom they care.